Copper ions binding in cu‐alginate gelation - Rodrigues, Joaquim Rui (2017)
Alginate polysaccharide forms viscous aqueous dispersions and has the ability to form gels in the presence of divalent cations such as calcium and copper. In this work, we have studied cooper ions binding during Cu‐alginate gelation, obtaining quantitative information about the amount and kinetics of cation binding. Our results indicate that copper binding during gelation occurs until a Langmuir‐type equilibrium is reached between bound and free ions in the gel‐contacting solution. The kinetics of metal ions binding can be modeled using Ritchie equation–derived models, allowing the prediction of ionic binding and gel formation temporal evolution. The ratio between cationic and polysaccharide quantities in the gelation system determines the kinetics of gelation and the characteristics of the gel formed. The experimental results and models applied in the work give more insights on alginate gelation and contribute to a reliable design and control of production methods for alginate gel structures.